Realization with fabrication of double-gate MOSFET based differential amplifier. (September 2019) - Pakaree, Japheth E.; Srivastava, Viranjay M.
Abstract: This research work designed a differential amplifier with Double-Gate (DG) MOSFET which can be used in electronic devices at Micro- and Nano-technology level. The DG MOSFET has been selected due to its minimal impurity scattering, high current drive, and better control of short channel effects as compared to Diodes, BJTs, and other MOSFETs. Configurations of the differential amplifier have been considered for DG MOSFET. The DG MOSFET based differential amplifier has been analysed with its small signal model, after that it has been fabricated and tested for various parameters such as differential mode gain, common mode gain, Common Mode Rejection Ratio (CMRR), and frequency response. The testing process results the differential mode gain (differential output) −8.69 V/V, common mode voltage gain (single-ended) -0.40 V/V, CMRR 19.06 dB (single-ended output) and simulated frequency response 32 MHz .